Designer gapped and tilted Dirac cones in lateral graphene superlattices - A. Wild; R. R. Hartmann; E. Mariani; M. E. Portnoi (APL Quantum)
We show that a planar array of bipolar waveguides in graphene can be used to engineer gapped and tilted two-dimensional Dirac cones within the electronic band structure. The presence of these gapped and tilted Dirac cones is demonstrated through a superlattice tight-binding model and verified using a transfer matrix calculation. By varying the applied gate voltages, the tilt parameter of these Dirac cones can be controlled, and their gaps can be tuned to fall in the terahertz range. The possibility of gate-tunable gapped Dirac cones gives rise to terahertz applications via interband transitions and designer Landau level spectra, both of which can be controlled via Dirac cone engineering. We anticipate that our paper will encourage Dirac cone tilt and gap engineering for gate-tunable device applications in lateral graphene superlattices.